Composite heat-conducting filler and preparation method thereof, heat-conducting silicone rubber and preparation method thereof, and application of heat-conducting silicone rubber

By using modified spherical boron nitride, sheet boron nitride and aluminum hydroxide composite thermal filler in thermal silicone rubber, the existing thermal silicone rubber has solved the problems of high density, high viscosity and low flame retardant grade, and the excellent performance of high thermal conductivity, low density, low viscosity and high flame retardant grade is achieved.

CN119570115AActive Publication Date: 2025-03-07SHENZHEN XINYA NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411762382.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

While increasing the thermal conductivity coefficient, existing thermal silicone rubbers lead to high density, high viscosity and low flame retardant grade, which cannot effectively solve the problem of thermal aggregation in electronic products.

Method used

Spherical boron nitride, sheet boron nitride and aluminum hydroxide are used as composite thermal conductivity fillers, and modified by silane coupling agent to make the filler hydrophobic, improve its compatibility with silicone rubber, thereby increasing the filler volume and thermal conductivity of the filler.

Benefits of technology

It realizes the high thermal conductivity, low density, low viscosity and high flame retardant grade of thermally conductive silicone rubber, which can quickly and effectively dissipate heat and improve the service life of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168026930000071
    Figure BDA0005168026930000071
  • Figure BDA0005168026930000081
    Figure BDA0005168026930000081
Patent Text Reader

Abstract

The invention discloses a composite heat-conducting filler and a preparation method thereof, heat-conducting silicone rubber and a preparation method thereof, and application of the heat-conducting silicone rubber, and belongs to the technical field of heat-conducting materials. The key point of the technical scheme is that the heat-conducting filler comprises spherical boron nitride, flaky boron nitride, aluminum hydroxide and a silane coupling agent; the mass ratio of the spherical boron nitride to the flaky boron nitride to the aluminum hydroxide is (8-12): (2-4): (7-10), and the addition amount of the silane coupling agent is 0.8-3.2% of the total amount of the spherical boron nitride, the flaky boron nitride and the aluminum hydroxide, so that the composite heat-conducting filler provided by the invention is high in filling amount, high in heat conductivity coefficient and good in flame-retardant effect, and after the filler is applied to silicone rubber, the flame-retardant effect is good. The silicone rubber has the excellent performance of high heat conductivity, low density, low viscosity and high flame retardant grade, heat generated by heat dissipation components can be quickly and effectively conducted out, and the effect of prolonging the service life of the components is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat-conducting materials, and in particular to a composite heat-conducting filler and a preparation method thereof, a heat-conducting silicone rubber and a preparation method thereof, and applications of the heat-conducting silicone rubber. Background Art

[0002] In recent years, electronic products have developed rapidly towards miniaturization and high power, which has put forward higher requirements for the performance of electronic products, especially heat dissipation, fire prevention and lightweight performance. At present, electronic products generally have the problem of heat accumulation. During use, a large amount of heat will be generated in a short period of time. The generated heat must be dissipated in time, otherwise it will directly affect the reliability and service life, and may also cause fire.

[0003] In order to improve the thermal conductivity, traditional thermally conductive silicone rubber adds a large amount of thermally conductive fillers, such as aluminum oxide and zinc oxide. However, these fillers have low thermal conductivity, poor flame retardant effect and high density, which will cause the silicone rubber to have low thermal conductivity, low flame retardant grade, high density and high viscosity. Summary of the invention

[0004] In order to solve the problems in the prior art, the present invention provides a composite thermally conductive filler and a preparation method thereof, a thermally conductive silicone rubber and a preparation method thereof, and applications of the thermally conductive silicone rubber. The composite thermally conductive filler provided in the present application has a high filling amount, a high thermal conductivity coefficient, and a good flame retardant effect. After the filler is applied to silicone rubber, the silicone rubber has excellent properties of high thermal conductivity, low density, low viscosity, and a high flame retardant grade. The heat generated by the heat dissipation components can be quickly and effectively conducted away, thereby increasing the service life of the components.

[0005] The first aspect of the present invention is to provide a composite thermal conductive filler. The following technical solution is adopted: A composite thermally conductive filler, comprising spherical boron nitride, flaky boron nitride, aluminum hydroxide and a silane coupling agent, wherein the mass ratio of the spherical boron nitride, flaky boron nitride and aluminum hydroxide is (8-12):(2-4):(7-10), and the added amount of the silane coupling agent is 0.8-3.2% of the total amount of the spherical boron nitride, flaky boron nitride and aluminum hydroxide.

[0006] By adopting the above technical scheme, the surfaces of spherical boron nitride, flaky boron nitride and aluminum hydroxide contain hydroxyl groups, which are hydrophilic substances. When preparing silicone rubber, the compatibility between the filler and the base rubber is poor, the high oil absorption value leads to a low filler filling amount, high product viscosity and low thermal conductivity. After the filler is modified by a silane coupling agent, the methoxy or ethoxy functional groups of the silane coupling agent can be hydrolyzed into hydroxyl groups, and react with the hydroxyl groups on the surface of the filler to turn the filler into a hydrophobic substance with hydrophobicity, so that the modified filler and the base rubber have good compatibility, the low oil absorption value can significantly increase the filler filling amount, and the prepared silicone rubber has a low viscosity, a high thermal conductivity and a high flame retardant grade.

[0007] Preferably, the particle size of the spherical boron nitride is 40-70 μm, the particle size of the flaky boron nitride is 0.8-3.2 μm, and the particle size of the aluminum hydroxide is 13-22 μm.

[0008] By adopting the above technical solution, spherical boron nitride has a significant effect on improving the thermal conductivity of fillers. However, due to the gaps and clearances between the fillers, the contact between the filler particles is not tight enough, thereby reducing the thermal conductivity effect. By adding small-particle-size flake boron nitride, the contact between the filler particles is made closer, which can significantly improve the thermal conductivity. The addition of aluminum hydroxide can not only improve the flame retardant effect of the filler, but also the interaction and contact between the three fillers of different particle sizes are closer, and the viscosity is lower, thereby increasing the overall amount of filler added, thereby improving the thermal conductivity.

[0009] The second aspect of the present invention is to provide a method for preparing a composite thermally conductive filler, comprising the following steps: S1. Stirring and mixing spherical boron nitride, flake boron nitride and aluminum hydroxide to obtain a mixture; S2. Add a silane coupling agent to the mixture obtained in step S1, and stir the mixture at a temperature of 90-130° C. for 50-120 min to obtain a composite thermal conductive filler.

[0010] By adopting the above technical scheme, when the reaction temperature of the silane coupling agent and the filler is too low, the degree of reaction between the hydrolyzed hydroxyl groups of the silane coupling agent and the hydroxyl groups on the surface of the filler is insufficient, and the modification effect is weakened. However, when the reaction temperature is too high, the coupling agent is easy to volatilize, which will also lead to a weakening of the modification effect. Therefore, when the reaction temperature of the silane coupling agent and the filler is limited to the range of 90-130°C in the present application, the modification effect of the silane coupling agent on the filler can be effectively improved.

[0011] The third aspect of the present invention is to provide a thermally conductive silicone rubber, which comprises, by weight, 100 parts of a base rubber, 10-50 parts of a diluent, 0.3-3.2 parts of a crosslinking agent, 0.3-3.2 parts of a catalyst, and 800-1500 parts of a composite thermally conductive filler obtained according to any one of claims 1-2.

[0012] Preferably, the base glue is one or both of alkoxy silicone oil and hydroxy silicone oil.

[0013] Preferably, the diluent is one or both of dimethyl silicone oil and MDT silicone oil.

[0014] Preferably, the crosslinking agent is one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane and propyltriethoxysilane.

[0015] Preferably, the catalyst is one or more of dibutyltin dilaurate, dibutyltin diacetate, diisopropyl di(ethyl acetoacetate) titanate, tetrabutyl titanate, di(acetylacetonate)-1,3-propanedioxytitanium, and tetraisopropyl titanate.

[0016] A fourth aspect of the present invention is to provide a method for preparing a thermally conductive silicone rubber, comprising the following steps: S1. Stir the base rubber, diluent and composite thermal conductive filler under vacuum at 90-130° C. for 40-130 min to obtain a mixture; S2. Cool the mixture obtained in step S1 to room temperature, add a crosslinking agent and a catalyst, and stir and mix under vacuum for 50-130 min to obtain thermal conductive silicone rubber.

[0017] A fifth aspect of the present invention is to provide an application of thermally conductive silicone rubber in the fields of electronic appliances and power adapters.

[0018] In summary, the present invention has the following beneficial effects: 1. The present application simultaneously adds spherical boron nitride with a particle size of 40-70 μm, flake boron nitride with a particle size of 0.8-3.2 μm and aluminum hydroxide with a particle size of 13-22 μm, so that the spherical fillers are in point-to-point contact with each other, and the flake fillers and spherical fillers are in surface and point contact with each other. Moreover, when the mass ratio of spherical boron nitride, flake boron nitride and aluminum hydroxide is limited to the range of (8-12): (2-4): (7-10), more contact points can be generated between the fillers, so that the filler filling amount is high, and the thermal conductivity of the filler can be effectively improved. At the same time, the particle size difference between spherical boron nitride and flake boron nitride is large. Adding aluminum hydroxide with a moderate particle size can make the contact between the filler particles closer. Under the joint action of the three, the viscosity is lower, thereby increasing the overall addition amount of the filler and further improving the thermal conductivity.

[0019] 2. In this application, spherical boron nitride, flaky boron nitride and aluminum hydroxide are modified by using a silane coupling agent, so that the spherical boron nitride, flaky boron nitride and aluminum hydroxide have hydrophobicity and low oil absorption value. At the same time, the modified filler has good compatibility with the base rubber in the silicone rubber, so that the viscosity of the filler after mixing with the base rubber is low, thereby reducing the amount of cross-linking agent and catalyst, and increasing the overall amount of filler added, so that the prepared silicone rubber has excellent properties of high thermal conductivity, low density, low viscosity and high flame retardant grade, which can improve the service life and work efficiency of components. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below with reference to the embodiments.

[0021] The raw materials used in this application are all commercially available.

[0022] Example 1 A method for preparing a composite thermally conductive filler comprises the following steps: S1. Add spherical boron nitride with a particle size of 40 μm, flake boron nitride with a particle size of 0.8 μm, and aluminum hydroxide with a particle size of 13 μm into a high-speed mixer in a weight ratio of 8:2:7, and stir and mix at a stirring speed of 110 r / min for 20 minutes to obtain a mixture; S2. Add 0.8% of the total weight of decyltrimethoxysilane, which accounts for spherical boron nitride, flaky boron nitride and aluminum hydroxide, to the mixture obtained in step S1, and stir the mixture at a temperature of 90° C. and a speed of 500 r / min for 120 min to obtain a composite thermal conductive filler.

[0023] Example 2 A method for preparing a composite thermally conductive filler comprises the following steps: S1. Add spherical boron nitride with a particle size of 40 μm, flake boron nitride with a particle size of 0.8 μm, and aluminum hydroxide with a particle size of 13 μm into a high-speed mixer at a weight ratio of 10:3:8, and stir and mix for 15 minutes at a stirring speed of 100 r / min to obtain a mixture; S2. Add propyltriethoxysilane accounting for 1.5% of the total weight of spherical boron nitride, flaky boron nitride and aluminum hydroxide to the mixture obtained in step S1, and stir the mixture at a temperature of 110° C. and a speed of 500 r / min for 90 minutes to obtain a composite thermal conductive filler.

[0024] Example 3 A method for preparing a composite thermally conductive filler comprises the following steps: S1. Add spherical boron nitride with a particle size of 40 μm, flake boron nitride with a particle size of 0.8 μm, and aluminum hydroxide with a particle size of 13 μm into a high-speed mixer in a weight ratio of 12:4:10, and stir and mix for 20 minutes at a stirring speed of 110 r / min to obtain a mixture; S2. Add 3.2% of hexadecyltrimethoxysilane, which accounts for the total weight of spherical boron nitride, flaky boron nitride and aluminum hydroxide, to the mixture obtained in step S1, and stir the mixture at a temperature of 130° C. and a speed of 500 r / min for 50 minutes to obtain a composite thermal conductive filler.

[0025] Example 4 A method for preparing a composite thermally conductive filler, which differs from Example 2 in that the particle size of the filler is different, specifically: the particle size of spherical boron nitride is 50 μm, the particle size of flaky boron nitride is 2.5 μm, and the particle size of aluminum hydroxide is 18 μm, and the rest are the same as Example 2.

[0026] Example 5 A method for preparing a composite thermally conductive filler, which differs from Example 2 in that the particle size of the filler is different, specifically: the particle size of spherical boron nitride is 70 μm, the particle size of flaky boron nitride is 3.2 μm, and the particle size of aluminum hydroxide is 22 μm, and the rest are the same as Example 2.

[0027] Example 6 A method for preparing a composite thermally conductive filler, which differs from Example 2 in that the particle size of the filler is different, specifically: the particle size of spherical boron nitride is 30 μm, the particle size of flaky boron nitride is 0.5 μm, and the particle size of aluminum hydroxide is 10 μm, and the rest are the same as Example 2.

[0028] Example 7 A method for preparing a composite thermally conductive filler, which differs from Example 2 in that the particle size of the filler is different, specifically: the particle size of spherical boron nitride is 75 μm, the particle size of flaky boron nitride is 3.5 μm, and the particle size of aluminum hydroxide is 25 μm, and the rest are the same as Example 2.

[0029] Comparative Example 1 A method for preparing a composite thermally conductive filler is different from that of Example 2 in that there is no spherical boron nitride in the composite thermally conductive filler in step S1, and the rest is the same as that of Example 2.

[0030] Comparative Example 2 A method for preparing a composite thermally conductive filler is different from that of Example 2 in that the composite thermally conductive filler in step S1 does not contain flaky boron nitride, and the rest is the same as that of Example 2.

[0031] Comparative Example 3 A method for preparing a composite thermally conductive filler is different from that of Example 2 in that the composite thermally conductive filler in step S1 does not contain aluminum hydroxide, and the rest is the same as that of Example 2.

[0032] Comparative Example 4 A method for preparing a composite thermally conductive filler is different from that of Example 2 in that no silane coupling agent is used to modify the composite thermally conductive filler in step S1, and the rest is the same as that of Example 2.

[0033] Comparative Example 5 A method for preparing a composite thermally conductive filler, which is different from Example 2 in that the weight ratio of spherical boron nitride to flaky boron nitride and aluminum hydroxide is 5:5:12, and the rest is the same as Example 2.

[0034] Comparative Example 6 A method for preparing a composite thermally conductive filler, which is different from Example 2 in that the weight ratio of spherical boron nitride to flaky boron nitride and aluminum hydroxide is 15:1:5, and the rest is the same as Example 2.

[0035] The composite thermally conductive fillers obtained in the above Examples 1-7 and Comparative Examples 1-6 are applied to thermally conductive silicone rubber, wherein the crosslinking agent in the thermally conductive silicone rubber can be one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, and propyltriethoxysilane, and the effects that can be achieved are basically the same. In the application examples of this application, methyltrimethoxysilane is used as an example for illustration; The catalyst may be one or more of dibutyltin dilaurate, dibutyltin diacetate, di(ethyl acetoacetate) diisopropyl titanate, tetrabutyl titanate, di(acetylacetonate)-1,3-propanedioxytitanium, and tetraisopropyl titanate, and the effects that can be achieved are basically the same. In the application examples of this application, di(ethyl acetoacetate) diisopropyl titanate is used as an example; the details are as follows: Application Example 1 A method for preparing a thermally conductive silicone rubber comprises the following steps: S1, adding 100 kg of alkoxy silicone oil, 10 kg of dimethyl silicone oil, and 800 kg of the composite thermal conductive filler obtained in Example 1 into a kneader, and vacuum stirring for 130 min under the conditions of a vacuum degree of -0.1 MPa and a temperature of 90° C. to obtain a mixture; S2. After cooling the mixture obtained in step S1 to room temperature, 0.3 kg of methyltrimethoxysilane and 0.3 kg of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was stirred and mixed for 130 min under the conditions of vacuum degree of -0.095 MPa, stirring speed of 60 r / min, and dispersion speed of 200 r / min. Then, the material was discharged under the protection of inert gas to obtain thermal conductive silicone rubber.

[0036] Application Example 2 A method for preparing a thermally conductive silicone rubber comprises the following steps: S1, adding 100 kg of hydroxy silicone oil, 25 kg of MDT silicone oil, and 1200 kg of the composite thermal conductive filler obtained in Example 1 into a kneader, and vacuum stirring for 100 min under the conditions of a vacuum degree of -0.1 MPa and a temperature of 120° C. to obtain a mixture; S2. After cooling the mixture obtained in step S1 to room temperature, 1.8 kg of methyltrimethoxysilane and 1.6 kg of di(ethyl acetoacetate)titanate diisopropyl were added, and the mixture was stirred and mixed for 100 min under the conditions of vacuum degree of -0.095 MPa, stirring speed of 65 r / min, and dispersion speed of 250 r / min. Then, the material was discharged under the protection of inert gas to obtain thermal conductive silicone rubber.

[0037] Application Example 3 A method for preparing a thermally conductive silicone rubber comprises the following steps: S1, adding 100 kg of alkoxy silicone oil, 50 kg of dimethyl silicone oil, and 1500 kg of the composite thermal conductive filler obtained in Example 1 into a kneader, and stirring under vacuum for 40 min at a vacuum degree of -0.1 MPa and a temperature of 130° C. to obtain a mixture; S2. After cooling the mixture obtained in step S1 to room temperature, 3.2 kg of methyltrimethoxysilane and 3.2 kg of di(ethyl acetoacetate)titanate diisopropyl were added, and the mixture was stirred and mixed for 50 minutes under the conditions of vacuum degree of -0.095 MPa, stirring speed of 60 r / min, and dispersion speed of 230 r / min. Then, the material was discharged under the protection of inert gas to obtain thermal conductive silicone rubber.

[0038] Application Example 4 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 2, and the rest is the same as that of Application Example 2.

[0039] Application Example 5 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 3, and the rest is the same as that of Application Example 2.

[0040] Application Example 6 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 4, and the rest is the same as that of Application Example 2.

[0041] Application Example 7 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 5, and the rest is the same as that of Application Example 2.

[0042] Application Example 8 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 6, and the rest is the same as that of Application Example 2.

[0043] Application Example 9 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Example 7, and the rest is the same as that of Application Example 2.

[0044] Application Comparative Example 1 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 1, and the rest is the same as that of Application Example 2.

[0045] Application Comparative Example 2 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 2, and the rest is the same as that of Application Example 2.

[0046] Application Comparative Example 3 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 3, and the rest is the same as that of Application Example 2.

[0047] Application Comparative Example 4 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 4, and the rest is the same as that of Application Example 2.

[0048] Application Comparative Example 5 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 5, and the rest is the same as that of Application Example 2.

[0049] Application Comparative Example 6 A method for preparing a thermally conductive silicone rubber is different from that of Application Example 2 in that the composite thermally conductive filler adopts the composite thermally conductive filler obtained in Comparative Example 6, and the rest is the same as that of Application Example 2.

[0050] Comparison Example A method for preparing a thermally conductive silicone rubber, which is different from Application Example 2 in that the composite thermally conductive filler is composed of aluminum oxide and zinc oxide, and the weight ratio of aluminum oxide to zinc oxide is 1:1, and the rest is the same as Application Example 2.

[0051] Performance Test: The viscosity, density, thermal conductivity, tensile strength and flame retardant grade of the thermally conductive silicone rubber obtained in the above application examples and the application comparison examples were tested. The test results are shown in Table 1, wherein the viscosity: is tested according to GB / T2794-2013; the density is tested according to GB / T13354-1992; the thermal conductivity is tested according to ISO / DIS22007; the tensile strength is tested according to ASTM D412; and the flame retardant grade is tested according to UL94.

[0052] Table 1 Silicone rubber test results From Table 1, we can see that: The viscosity of the silicone rubber obtained in the application example of the present application is much lower than that of the silicone rubber in the control example, while the thermal conductivity, tensile strength and flame retardancy are much higher than those in the control example, indicating that the composite thermally conductive filler obtained in the present application can be used in silicone rubber to effectively reduce the viscosity of the silicone rubber, while also improving the thermal conductivity and flame retardancy of the silicone rubber.

[0053] In the case where the composite thermally conductive fillers are all the composite thermally conductive fillers obtained in Example 1, the viscosity of the thermally conductive silicone rubber obtained in Application Examples 1-3 first decreases and then increases with the increase in the amount of the composite thermally conductive filler added, and the thermal conductivity and tensile strength show a trend of first increasing and then decreasing. It can be seen that when the amount of the composite thermally conductive filler added is within the range specified in the present application, the thermal conductivity and tensile strength of the silicone rubber can be effectively improved, and at the same time, the silicone rubber can also have a lower viscosity.

[0054] Compared with Application Example 2, Application Example 8-9 shows that when the particle sizes of spherical boron nitride, flaky boron nitride and aluminum hydroxide exceed the limits of this application, the adhesion of the silicone rubber obtained in Application Example 8 is significantly increased, and the viscosity of the silicone rubber obtained in Application Example 9 is reduced, but the thermal conductivity and tensile strength of the silicone rubber obtained in Application Examples 8-9 are reduced. It can be seen that when the particle sizes of spherical boron nitride, flaky boron nitride and aluminum hydroxide are within the range of this application, not only can the silicone rubber have a lower viscosity, but the thermal conductivity and tensile strength of the silicone rubber can also be improved.

[0055] Compared with Application Example 2, when the composite thermally conductive filler lacks spherical boron nitride or flaky boron nitride or aluminum hydroxide or silane coupling agent, the viscosity of the silicone rubber obtained by Application Comparative Examples 1-4 is significantly increased, and the thermal conductivity and tensile strength of the silicone rubber are reduced compared with Application Example 2. It can be seen that the combined use of spherical boron nitride, flaky boron nitride, aluminum hydroxide and silane coupling agent in the present application effectively reduces the viscosity of the silicone rubber, and also improves the thermal conductivity and tensile strength of the silicone rubber.

[0056] Compared with Application Example 2, when the ratio of spherical boron nitride, flaky boron nitride and aluminum hydroxide is not within the range specified in the present application, the silicone rubber obtained by Application Comparative Examples 5-6 has high viscosity, low thermal conductivity and low tensile strength. This further illustrates that the weight ratio of spherical boron nitride, flaky boron nitride and aluminum hydroxide has a relatively large influence on the performance of silicone rubber.

[0057] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite thermally conductive filler, characterized in that: The thermal conductive filler comprises spherical boron nitride, flaky boron nitride, aluminum hydroxide and a silane coupling agent. The mass ratio of the spherical boron nitride, flaky boron nitride and aluminum hydroxide is (8-12): (2-4): (7-10). The added amount of the silane coupling agent is 0.8-3.2% of the total amount of the spherical boron nitride, flaky boron nitride and aluminum hydroxide.

2. A composite thermally conductive filler according to claim 1, characterized in that: The particle size of the spherical boron nitride is 40-70 μm, the particle size of the flaky boron nitride is 0.8-3.2 μm, and the particle size of the aluminum hydroxide is 13-22 μm.

3. A method for preparing the composite thermally conductive filler according to any one of claims 1 to 2, characterized in that: The steps include: S1. Stirring and mixing spherical boron nitride, flake boron nitride and aluminum hydroxide to obtain a mixture; S2. Add a silane coupling agent to the mixture obtained in step S1, and stir the mixture at a temperature of 90-130° C. for 50-120 min to obtain a composite thermal conductive filler.

4. A thermally conductive silicone rubber, characterized in that: Calculated by weight, it comprises 100 parts of base glue, 10-50 parts of diluent, 0.3-3.2 parts of cross-linking agent, 0.3-3.2 parts of catalyst and 800-1500 parts of the composite thermal conductive filler obtained in any one of claims 1-2.

5. The thermally conductive silicone rubber according to claim 4, characterized in that: The base glue is one or both of alkoxy silicone oil and hydroxy silicone oil.

6. The thermally conductive silicone rubber according to claim 4, characterized in that: The diluent is one or both of dimethyl silicone oil and MDT silicone oil.

7. The thermally conductive silicone rubber according to claim 4, characterized in that: The crosslinking agent is one or more of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane and propyltriethoxysilane.

8. The thermally conductive silicone rubber according to claim 4, characterized in that: The catalyst is one or more of dibutyltin dilaurate, dibutyltin diacetate, di(ethyl acetoacetate) diisopropyl titanate, tetrabutyl titanate, di(acetylacetonate)-1,3-propanedioxytitanium, and tetraisopropyl titanate.

9. A method for preparing the thermally conductive silicone rubber according to any one of claims 4 to 8, characterized in that: The method comprises the following steps: S1, stirring the base glue, the diluent and the composite thermal conductive filler under vacuum at 90-130° C. for 40-130 minutes to obtain a mixture; S2. Cooling the mixture obtained in step S1 to room temperature, adding a crosslinking agent and a catalyst, and stirring and mixing under vacuum conditions for 50-130 minutes to obtain a thermally conductive silicone rubber.

10. Use of the thermally conductive silicone rubber according to any one of claims 4 to 8 in the fields of electronic appliances and power adapters.

Citation Information

Patent Citations

  • Composite heat conduction material, silicone rubber and preparation method and application thereof

    CN111875852A

  • Flame-retardant insulating high-thermal-conductivity TPE material for automobile charging wire and preparation method of TPE material

    CN112592555A

  • Polymer-based composite heat conduction material as well as preparation method and application thereof

    CN113912914A

  • Composite heat-conducting filler, high-heat-conducting silicone grease as well as preparation method and application of high-heat-conducting silicone grease

    CN116333374A

  • Heat-conducting filler, preparation method thereof and epoxy molding compound

    CN118420976A